Financialization, Government Subsidies, and Enterprise Technological Innovation: Empirical Evidence from Listed Manufacturing Firms - Ke, Meiling (Journal of Theory and Practice in Economics and Management, 2024)
This study examines the relationship between the financialization of non-financial enterprises and their technological innovation using panel data from A-share manufacturing firms listed on the Shanghai and Shenzhen stock exchanges from 2012 to 2018. Grounded in the theories of financing constraints and information asymmetry, our findings indicate that the financialization of Chinese manufacturing enterprises exhibits a “crowding out effect” rather than a “reservoir effect” on technological innovation. Specifically, financialization tends to impede corporate investment in technological innovation. Moreover, government subsidies significantly mitigate this crowding-out effect. The results serve as a cautionary note for financially-oriented manufacturing enterprises and offer policy recommendations for addressing the phenomenon of enterprise financialization.